Right To Constitutional Remedies- A Study Of Constitutional Arrangements To Protect Fundamental Rights In Sri Lanka - Kosalai Mathan (University of Jaffna, 2014)
Chapter III of the Constitution of the Democratic Socialist Republic of Sri Lanka 1978 guarantees fundamental rights from Article 10 to 14.Article 17 being a provision in the chapter entitled “ Fundamental Rights” the right to move the Supreme Court, when a fundamental right has been infringed or is about to be infringed by executive or administrative action, is in itself a fundamental right . Though Constitution provides enforcement mechanism, rights have not been protected and promoted in Sri Lanka. Article 126(2) of the Constitution provides a one month time period for a person to file an application of an infringement of right. One month is hardly sufficient to obtain legal advice and documents to present a prima facie case. Article 126(2) of the constitution provides that such an application may be made by such person himself or by an Attorney-at-law on his behalf.The public interest litigation is not seriously considered in Sri Lanka like in India. Article 17 speaks of infringement of fundamental rights by executive or administrative action and legislative and judicial actions have been purposely omitted from the scope of Article 17. The main objective of this study is to understand the present state of law relating to fundamental rights and to identify possible areas for widening the scope of rights both by constitutional amendment and judicial activism